A Framework For Utilizing IMC In Developing Stronger Branding For Educational Institutions - Binsar Marbun (UNIVED Press, 2025)
The background of this study focuses on the intense competition in the education sector, where educational institutions must adopt innovative approaches to attract and retain students. However, traditional communication strategies are no longer sufficient. The primary issue identified is the lack of understanding regarding the potential and implementation of Integrated Marketing Communication (IMC) in strengthening educational branding. This study employs a qualitative approach to explore perceptions, practices, and challenges in implementing IMC. IMC is a strategic approach that integrates various marketing communication tools to deliver consistent messages and enhance brand image. This study proposes an IMC-based framework, incorporating strategies such as PENCILS (Publications, Events, News, Community Involvement, Information/Image, Lobbying and Negotiation, and Social Responsibility) to strengthen institutional branding. The findings indicate that IMC implementation not only enhances competitiveness but also supports the development of long-term relationships with stakeholders. The study recommends better IMC integration through strategic coordination, personnel training, and digital technology optimization for effective branding.